The Relationship Between Asta Brata Leadership, School Culture, and The Character of Elementary School Students in Pupuan Tabanan - Rahmadani, Komang Yolanda; Werang, Basilius Redan; Riastini, Putu Nanci (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2026)
Character education constitutes a fundamental component of the educational system, as it plays a vital role in fostering students’ moral, ethical, and human values. The persistence of behavioral issues among elementary school students, including low levels of discipline, dishonesty, and bullying, indicates that efforts to strengthen character education continue to face challenges. The development of students’ character is shaped by multiple factors, particularly school culture and principals’ leadership practices. Asta Brata leadership, rooted in Balinese local wisdom, embodies noble values that are considered relevant for cultivating a positive school culture and promoting students’ character development. This study seeks to investigate the relationships among Asta Brata leadership, school culture, and the character of elementary school students in Pupuan, Tabanan. A quantitative approach was adopted, employing an ex post facto research design with a survey method. Data were gathered through questionnaires and analyzed using correlation analysis. The findings reveal significant relationships between Asta Brata leadership and school culture, Asta Brata leadership and students’ character, as well as school culture and students’ character, with correlation levels ranging from strong to very strong. These results demonstrate that stronger implementation of Asta Brata leadership values, accompanied by a more positive school culture, contributes to improved character development among elementary school students. The findings of this study are expected to provide valuable insights for school principals and educational policymakers in enhancing character education at the elementary school level.